A study of the Philippines Social Security System, its assistance of private school teachers of the province of Agusan - Rosales, Socorro (Alkuino) 1924- (s.n.], 1969)
The aim of the study is to determine the organization and functions of the Philippine Social Security System and the extent of its assistance in a certain group of members, specifically the Agusan Private School Teachers. The study has been made in an attempt to disseminate information the vital role of the SSS to effect an economic and nationalistic development in the country, to make clear its benefits extended to its members and to bring about suggestions on the needed improvement of the system which may be important for a periodic assessment of the needs of SSS members and for further consideration of the benefits extended them at present and in the future.